(untitled) (Upper Saddle River, N.J., 2009)
Clean Code is divided into three parts. The first describes the principles, patterns, and practices of writing clean code. The second part consists of several case studies of increasing complexity. Each case study is an exercise in cleaning up code—of transforming a code base that has some problems into one that is sound and efficient. The third part is the payoff: a single chapter containing a list of heuristics and “smells” gathered while creating the case studies. The result is a knowledge base that describes the way we think when we write, read, and clean code. This book is a must for any developer, software engineer, project manager, team lead, or systems analyst with an interest in producing better code.
Keywords: Phần mềm máy tính,Computer software; Độ tin cậy.,Reliability